2017
DOI: 10.14326/abe.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Novel Electronic Musical Instrument with Pre-Programmed Score for the Disabled to Enjoy Playing Music

Abstract: We have developed a novel electronic musical instrument with a pre-programmed score, called Cymis, to help the disabled enjoy playing musical pieces. In 2008, eld experiments commenced at a nursing home (capacity 52 clients; average age 58.6; cerebral palsy 32 clients). The purpose of the present study was to demonstrate that Cymis is useful and effective for helping the severely disabled maintain or improve their quality of life. First, the accessibility of Cymis was revealed by the fact that 34 clients (63%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The display shows musical information on the screen, and when the user touches a note on the screen, the same note played with the speci ed instrument is sounded via a MIDI sound source. We have already reported that elderly people with impaired motor functions are able to play a piece of music with relatively simple touch movements [16]. Since the long-term goal of this study is to reduce the risk of developing dementia, and since the subjects are healthy adults, the volume is not constant but changes according to the strength of exhalation/inhalation, so that they can experience the pleasure of playing.…”
Section: Musical Instruments For Adult Beginnersmentioning
confidence: 97%
See 2 more Smart Citations
“…The display shows musical information on the screen, and when the user touches a note on the screen, the same note played with the speci ed instrument is sounded via a MIDI sound source. We have already reported that elderly people with impaired motor functions are able to play a piece of music with relatively simple touch movements [16]. Since the long-term goal of this study is to reduce the risk of developing dementia, and since the subjects are healthy adults, the volume is not constant but changes according to the strength of exhalation/inhalation, so that they can experience the pleasure of playing.…”
Section: Musical Instruments For Adult Beginnersmentioning
confidence: 97%
“…We are developing an electronic musical instrument, Cymis (Cyber Musical Instrument with Score) [16], which is a barrier-free electronic musical instrument that can be played easily by beginners of all ages, who do not fully understand musical scores. The human interface presented by Cymis is technologically novel in that it emphasizes the senses, and is characterized by information from its built-in musical score and its programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual sessions for MT were held twice a week, for 15 min per session in the evening, over 18 months. For the musical instrumental performance, we used an accessible digital musical instrument called the Cymis ( 21 ), which has a built-in programmed score and is played using touch panels and switches ( Figure 2 ). The technical novelty of the Cymis lies in its human interface devices that emphasize the sensory experience and is characterized by its built-in score information and program.…”
Section: Patient Informationmentioning
confidence: 99%
“…Despite the fact that accessible digital musical instruments can take into account the level of cognitive demands, previous studies have been conducted with patients with MCI, and it is not known whether such methods can be used by people with moderate to severe dementia or dementia with worsening behavioral and psychological symptoms of dementia (BPSD). We asked patients with severe dementia to use the accessible digital musical instrument Cymis (cyber musical instrument with score) ( 21 ), which has already been used in MT for patients with cerebral palsy, to assess whether they could play it when their cognitive function declined or when their BPSD worsened.…”
Section: Introductionmentioning
confidence: 99%